Effects of Oltipraz on the Glycolipid Metabolism and the Nrf2/HO-1 Pathway in Type 2 Diabetic Mice - Luo Y; Sun S; Zhang Y; Liu S; Zeng H; Li JE; Huang J; Fang L; Yang S; Yu P; Liu J (Drug Design, Development and Therapy)
Yunfei Luo,1,* Shaohua Sun,1,2,* Yuying Zhang,1,* Shuang Liu,1 Haixia Zeng,1 jin-E Li,1 Jiadian Huang,1 Lixuan Fang,1 Shiqi Yang,1 Peng Yu,1 Jianping Liu1,3,4 1Department of Endocrinology and Metabolism of the Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, 330031, People’s Republic of China; 2Department of Metabolism and Endocrinology, XinSteel Center Hospital, Xinyu, Jiangxi, 338000, People’s Republic of China; 3Institute for the Study of Endocrinology and Metabolism in Jiangxi Province, Nanchang, Jiangxi, 330031, People’s Republic of China; 4Branch of National Clinical Research Center for Metabolic Diseases, Nanchang, Jiangxi, 330031, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianping Liu, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, No. 1, Minde Road, Nanchang, Jiangxi, 330031, People’s Republic of China, Email ndefy14105@ncu.edu.cnPurpose: Oltipraz has various applications, including for treating cancer, liver fibrosis, and cirrhosis. However, its role in regulating metabolic processes, inflammation, oxidative stress, and insulin resistance in STZ-induced T2DM remains unclear. Hence, a comprehensive understanding of how oltipraz ameliorates diabetes, particularly inflammation and oxidative stress, is imperative.Methods: The negative control (NC), T2DM model (T2DM), and T2DM models treated with oltipraz (OLTI) and metformin (MET) were constructed. The RNA sequencing (RNA-Seq) was performed on the pancreatic tissues. H&E staining was conducted on the liver and pancreatic tissues. The intraperitoneal glucose tolerance test (IPGTT), blood glucose and lipids, inflammatory factors, and oxidative stress indexes were measured. qPCR and Western blotting examined the nuclear factor erythroid-derived 2-like 2 (Nrf2)/ hemoglobin-1 (HO-1) signaling pathway, cell apoptosis-related genes, and Reg3g levels. Immunofluorescence (IF) analysis of the pancreas was performed to measure insulin secretion.Results: A total of 256 DEGs were identified in OLTI_vs_T2DM, and they were mainly enriched in circadian rhythm, cAMP, AMPK, insulin, and MAPK signaling pathways. Moreover, Reg3g exhibits reduced expression in T2DM_vs_NC, and elevated expression in OLTI_vs_T2DM, yet remains unchanged in MET_vs_T2DM. OLTI reduced fasting blood glucose and alleviated T2DM-induced weight loss. It improved blood glucose and insulin resistance, decreased blood lipid metabolism, reduced inflammation and oxidative stress through the Nrf2/HO-1 signaling pathway, mitigated pancreatic and liver tissue injury, and enhanced pancreatic β-cell insulin secretion. OLTI exhibited anti-apoptosis effects in T2DM. Moreover, OLTI exhibits superior antioxidant activity than metformin.Conclusion: In summary, OLTI improves blood glucose and insulin resistance, decreases blood lipid metabolism, reduces inflammation and apoptosis, suppresses oxidative stress through the Nrf2/HO-1 signaling pathway, mitigates pancreatic and liver tissue injury, and enhances pancreatic β-cell insulin secretion, thereby mitigating T2DM symptoms. Moreover, Reg3g could be an important target for OLTI treatment of T2DM.Keywords: Oltipraz, T2DM, oxidation stress, Nrf2, inflammation